Competence of guidance and counseling teacher in developing helping relationship with student - - Yusi Riksa Yustiana, - Aas Saomah, - Suherman, (Universiti Pendidikan Sultan Idris, 2017)
Competence of guidance and counseling teacher in developing helping relationship with student by - Yusi Riksa Yustiana, - Aas Saomah, - Suherman,